MaterniCode: New Bioinformatic Pipeline to Detect Fetal Aneuploidies and Rearrangements Using Next-Generation Sequencing - Federico Gabrielli; Filomena Tiziana Papa; Fabio Di Pietro; Andreu Paytuví-Gallart; Daniel Julian; Walter Sanseverino; Cinzia Alfonsi (International Journal of Genomics)
Conclusion: MaterniCode has proven to be an innovative and highly efficient tool in the domain of NIPT, demonstrating excellent sensitivity and specificity. Its robust capability to effectively detect a wide range of complex chromosomal aberrations, including rare and subtle variations, positions it as a promising and valuable addition to prenatal diagnostic technologies. This enhancement to diagnostic precision significantly aids clinicians in making informed decisions during pregnancy management.